Solving Exponential Situations and Conceptualization Resolução de Situações Exponenciasi e Conceituação - Sureda Figueroa, Diana Patricia; Otero, María Rita (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2015)
Students have difficulty to use different representational systems. We use the Theory of Conceptual Fields in order to describe and analyze students’ responses to situations in various representational system: numerical, first order algebraic, graphic and verbal written. We conducted the study with 59 students (aged between 15-16 years old) of secondary school. From the analysis we show that students do not "translate" the results of a representational system to another. They can solve exponentially in a representational system (RS) but in a different exponential RS they solve it in a non-exponential way. This indicates that students construct operational invariants for each representational system. That is to say, they build and use different schemes for each one of them.